2010
DOI: 10.4236/health.2010.29150
|View full text |Cite
|
Sign up to set email alerts
|

Sexual assaults in therapeutic relationships: prevalence, risk factors and consequences

Abstract: A law has been passed in Germany (paragraph 174c StGB), which prohibits therapists from having sexual contact with their patients. This provides the background for a follow-up survey to the previous study completed by Becker- Fischer and Fischer in 1995. The results of this survey are discussed here on the basis of the current status of research concerning preva- lence and risk factors of sexual assaults in therapeutic relationships. The focus of the re- search lies in determining the specific condi- tions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The victims pointed to several short- and long-term consequences, such as disgust, outrage, anger, shame and powerlessness. These sentiments are in line with what is found in existing literature, namely the studies by Eichenberg et al (2010) and Hook and Devereux (2018) . Consequently, participants also suffered some changes in their daily lives, namely moving to another city, difficulty in trusting other people, fear of having sex and difficulty in establishing intimate relationships with a romantic partner.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The victims pointed to several short- and long-term consequences, such as disgust, outrage, anger, shame and powerlessness. These sentiments are in line with what is found in existing literature, namely the studies by Eichenberg et al (2010) and Hook and Devereux (2018) . Consequently, participants also suffered some changes in their daily lives, namely moving to another city, difficulty in trusting other people, fear of having sex and difficulty in establishing intimate relationships with a romantic partner.…”
Section: Discussionsupporting
confidence: 92%
“…In general, 86.5% of the sample under study exhibited negative results, with therapists causing serious damage in the lives of their patients. The findings emphasize different feelings and symptoms precipitated by the SV, including “(…) mistrust, isolation, feelings of shame and guilt, fear, depression and suicidal tendencies, anger and symptoms of post-traumatic stress disorder” ( Eichenberg et al, 2010 , p. 1,019).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Although this prohibition on physician-patient sexual relations is based on evidence that such relations harm patients and endanger their medical care [ 4 9 ], physician sexual misconduct has received inadequate attention from researchers [ 10 ]. Two recent studies [ 11 , 12 ] examined, in part, physician sexual misconduct among Canadian physicians, but no such U.S. national-level analyses have been published on this important public health problem since Public Citizen’s 1998 study, limited to medical board licensure actions [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…We focus here on those involving the offending therapist because our emphasis is on their assessment and treatment. Among others, primary individual characteristics of therapists who commit SBVs are male gender (although a relatively recent study found female therapists accounting for 28.8% of client sexual abuse, likely due to more females practicing psychotherapy than ever before; Eichenberg et al, 2010) and older age, a lack of emotionally intimate relationships outside of work, a personal history of abuse, a history of neglect by a parental figure, and grandiosity regarding their role as authority figures responsible for others. Additional personal findings include having questions about or problems about sexual identity or orientation, sexual dissatisfaction, anxiety and guilt, and having career stresses and uncertainties (Halter et al, 2007).…”
Section: Risks For Boundary Crossings and Violationsmentioning
confidence: 99%